Effect of Carrageenan Addition on the Quality of Bacterial Cellulose-Based Biodegradable Plastic from Coconut Water - Humaira, Alifah; Putra, Ananda (Journal of Natural Sciences, 2024)
Plastic is often used in daily life, resulting in a lot of plastic waste. Therefore, a solution is needed, namely the production of biodegradable plastic. This research aims to see the effect of carrageenan addition variation on the quality of bacterial cellulose-sorbitol-based biodegradable plastic from coconut water (Cocos nucifera) which includes mechanical properties testing (tensile strength, elongation, and moduulus young), biodegradation testing, and testing with FTIR and XRD instruments. In this study, sorbitol 30 % was used as a plasticizer with carrageenan variations of 0%, 0.5%, 1%, 1.5%, and 2%.  The mechanical properties test results obtained a maximum tensile strength value of 126.58 Mpa in the 2% carrageenan addition variation, where the tensile strength value has met SNI standards for synthetic plastics which ranges from 24.7-302 Mpa, the Modulus young value obtained is 980.46 Mpa, and the elongation value is 21.68%. For the biodegradation test, the plastic added with carrageenan increased and on the 15th day the plastic was completely degraded. On FTIR functional group analysis, no new groups were formed and on XRD analysis on the addition of carrageenan, the % crystallinity of the plastic was greater at 98.66% compared to bacterial cellulose 97.01%, and bacterial cellulose-sorbitol 95.79%.